Associations between major indices of physical development and fitness and the level of elite wrestler special work - Pryimakov, O.; Masenko, L.; Lachno, D. (Central European Journal of Sport Sciences and Medicine, 2015)
Objective: The objective of the given work consisted in studying associations between the major indices of physical development (PD) and physical fitness, on the one hand, and the level of special work capacity of elite wrestlers of different weight categories, on the other hand. Material: 147 Ukrainian athletes engaged in Greco-Roman, free-style wrestling and judo served as the subjects. The following methods of studies were used: anthropometry, caliperometry, dynamometry, methods of testing speed-strength fitness and special work capacity of wrestlers, statistical processing and computer modelling. Results: It has been demonstrated that skill level determines ratio and associations of morphometric and speed-strength indices, level of athletes` special work capacity. Enhancement of skill level results in augmentation of speed-strength fitness, increase of body circumferences, decrease of fat component content, gain of muscular component and muscular development index. Along with the increase of weight category the level of speed-strength fitness and special work capacity decreases. Respective mathematical models were developed. Conclusions. It is recommended to use the developed regression models for modelling, predicting and evaluating special work capacity of highly skilled wrestlers of light, middle and heavy weight categories.